Et senmiddelalderligt handelsnetværk: Flensborgkøbmanden Namen Jansens købmandsbog 1528-49 - Pajung, Stefan; Poulsen, Bjørn (Temp - tidsskrift for historie, 2014)
A late medieval trade network: The Flensburg merchant Namen Jansen’s account book 1528-1549 This article illustrates the importance of networks for the late medieval economy through the account book of the Flensburg merchant Namen Jansen. This source is unique in a Danish context and covers the period 1528-1549. Namen Jansen was a farmer’s son from the west coast of Schleswig and manages to create a number of trading networks. On the interregional and international market he was connected to 150-200 partners in Northern Germany, while he had between 800 and 900 contacts on the regional level, giving us an insight into rural patterns of consumption. A second account book by the peasant trader Anders Oggels demonstrates how Namen Jansen’s network was connected to and interacted with that of small scale traders. One of Namen Jansen’s main commodities was hops imported from Mecklenburg, which he sold to customers in Schleswig and Denmark at the main regional fairs. In conclusion, Namen Jansen exploited the opportunities opened by the east-west trade across Schleswig and the north-south going trade between Mecklenburg and Jutland with great flexibility. His trade and the composition of his network are at once unique and at the same time characteristic for merchants not only in Denmark and Schleswig - but throughout Northern Europe.